Differences in Subjective Cognitive Complaints Between Non-Demented Older Adults from a Memory Clinic and the Community - Markova, Hana; Nikolai, Tomas; Mazancova, Adela Fendrych; Cechova, Katerina; Sheardova, Katerina; Georgi, Hana; Kopecek, Miloslav; Laczó, Jan; Hort, Jakub; Vyhnalek, Martin (Journal of Alzheimer's disease, 2019)
BACKGROUND: Subjective cognitive complaints (SCCs) may represent an early cognitive marker of Alzheimer's disease (AD). There is a need to identify specific SCCs associated with an increased likelihood of underlying AD. OBJECTIVE: Using the Questionnaire of Cognitive Complaints (QPC), we evaluated the pattern of SCCs in a clinical sample of non-demented older adults in comparison to cognitively healthy community-dwelling volunteers (HV). METHODS: In total, 142 non-demented older adults from the Czech Brain Aging Study referred to two memory clinics for their SCCs were classified as having subjective cognitive decline (SCD, n = 85) or amnestic mild cognitive impairment (aMCI, n = 57) based on a neuropsychological evaluation. Furthermore, 82 age-, education-, and gender-matched HV were recruited. All subjects completed the QPC assessing the presence of specific SCCs in the last six months. RESULTS: Both SCD and aMCI groups reported almost two times more SCCs than HV, but they did not differ from each other in the total QPC score. Impression of memory change and Impression of worse memory in comparison to peers were significantly more prevalent in both SCD and aMCI groups in comparison to HV; however, only the latter one was associated with lower cognitive performance. CONCLUSION: The pattern of QPC-SCCs reported by SCD individuals was more similar to aMCI individuals than to HV. A complaint about memory change seems unspecific to pathological aging whereas a complaint about worse memory in comparison to peers might be one of the promising items from QPC questionnaire potentially reflecting subtle cognitive changes.
Keywords: Male; Aging; Middle Aged; poruchy paměti; subjective cognitive decline; kognitivní dysfunkce; Aged; mužské pohlaví; senioři; Cognitive Dysfunction; průzkumy a dotazníky; subjective cognitive complaints; Neuropsychological Tests; senioři nad 80 let; kognice; lidé; Memory Disorders; ženské pohlaví; Humans; Memory; paměť; Mild cognitive impairment; questionnaire of cognitive complaints; stárnutí; Aged, 80 and over; neuropsychologické testy; prodromal Alzheimer’s disease; Female; Surveys and Questionnaires; lidé středního věku; Cognition